Aerodynamic Characteristics of a Real 3D Flow around a Finite Wing (Global Journals of Research in Engineering, 2014)
This paper presents a new method of solution for the aerodynamics of finite-span wings which overcomes the difficulties of the previous methods A lot of disturbance is created in the air when an aeroplane flies It is through the study of these disturbances of the flow past the airfoil lots of design considerations are done In this paper we design a 3D air wing and solve the flow equations in a CFD solver and study the characteristics features of the flow around a finite wing and the effect of the tip vortices that are caused by the difference of pressures between the lower and upper portion around the tips on an air airfoil
Keywords: finite wing; real 3d flow; vortices; pressure differences; vortex flow